Developing strategies at the pre-service level to address critical teacher attraction and retention issues in Australian rural, regional and remote schools. - Boyd, Don; Terry, Emmy; Trinidad, Sue (Australia. Office for Learning and Teaching, 2013)
This is the report from a project that aimed to strengthen the capacity and credibility of universities to prepare rural, regional and remote educators, similar to the capacity and credibility that has been created in preparing Australia's rural, regional and remote health workers. It documents the journey, deliverables/outcomes and recommendations of the project. The project achieved the following broad outcomes and deliverables: Developing a pre-service training framework and rural, regional and remote studies curriculum modules linked to the National Professional Standards of Teachers; Developing models of rural, regional or remote experiences for pre-service teachers who may be teaching in a variety of different locations such as a small rural farming community; a regional mining community; or a remote Indigenous community; Linking theoretical and practical teaching and learning processes for example practical field experiences into the curriculum; Documenting ways in which the participation rates of regional students in Western Australian teacher education programs can be increased; Embedding collaborative strategies between rural, regional and remote teacher educators across four universities in Western Australia; Improving communication between teacher educators and regional authorities; and Expanding the research associated with rural, regional and remote education. [Executive summary, ed]